Utilization of Mathematical Software in Rejuvenating Senior Secondary School Students’ Interest in Geometry - Terungwa James, Age (Mathematics and Computer Science: Contemporary Developments Vol. 10, 2024)
Geometry is a branch of Mathematics that deals with the measurement and properties of points, lines, curves and surfaces. It provides ground for the development of Mathematical thinking, from concrete visualization to abstract reasoning and modeling. Students’ interest is one of the major factors that influence students’ learning and achievement. The study investigated how the use of mathematical software rejuvenates Secondary School (SS1) students’ interest in Geometry. The study used a quasi-experimental non-randomized pre-test post-test control group design. The sample comprised 457 out of 12,308 SS1 students in 308 Government grant-aided secondary schools in Benue State, Nigeria. The study had three research questions and three hypotheses that guided the research. Geometry Interest Inventory (GII) was the instrument used for data collection and it was duly validated by four experts in Mathematics Education and one expert in Measurement and Evaluation at the Federal University of Agriculture, Makurdi. The reliability coefficients of GII were calculated to be 0.96 using Cronbach Alpha. Data were collated and analyzed using Mean, Standard Deviation and Analysis of Covariance (ANCOVA). Answers were given to the research questions using the Mean and Standard Deviation and the research hypotheses were tested at 0.05 level of significance using ANCOVA. This study showed that the utilization of GeoEnzo software is a veritable strategy in the mathematics classroom. Results of the study revealed that students in the experimental group manifested greater (\(\bar{X}\)=3.21) interest in geometry taught than those in the control group (\(\bar{X}\)=2.69). The study also revealed improvement in interest (0.00 < 0.05) as being statistically significant. The experimental group revealed no gender differences in the levels of interest in Geometry concepts they were exposed to. It was therefore recommended among others, that teachers should use GeoEnZo in the teaching of Geometry as well as other Mathematics concepts. The school authorities should create an enabling environment for Mathematics teachers to access GeoEnZo to enable them to teach geometry effectively so as to enhance the interest of both male and female students.